A radial sampling strategy for uniform k‐space coverage with retrospective respiratory gating in 3D ultrashort‐echo‐time lung imaging. (18th February 2016) - Park, Jinil; Shin, Taehoon; Yoon, Soon Ho; Goo, Jin Mo; Park, Jang‐Yeon
Abstract : The purpose of this work was to develop a 3D radial‐sampling strategy which maintains uniform k ‐space sample density after retrospective respiratory gating, and demonstrate its feasibility in free‐breathing ultrashort‐echo‐time lung MRI. A multi‐shot, interleaved 3D radial sampling function was designed by segmenting a single‐shot trajectory of projection views such that each interleaf samples k ‐space in an incoherent fashion. An optimal segmentation factor for the interleaved acquisition was derived based on an approximate model of respiratory patterns such that radial interleaves are evenly accepted during the retrospective gating. The optimality of the proposed sampling scheme was tested by numerical simulations and phantom experiments using human respiratory waveforms. Retrospectively, respiratory‐gated, free‐breathing lung MRI with the proposed sampling strategy was performed in healthy subjects. The simulation yielded the most uniform k ‐space sample density with the optimal segmentation factor, as evidenced by the smallest standard deviation of the number of neighboring samples as well as minimal side‐lobe energy in the point spread function. The optimality of the proposed scheme was also confirmed by minimal image artifacts in phantom images. Human lung images showed that the proposed sampling scheme significantly reduced streak and ring artifacts compared with the conventional retrospective respiratory gating while suppressing motion‐related blurring compared with full sampling without respiratory gating. In conclusion, the proposed 3D radial‐sampling scheme can effectively suppress the image artifacts due to non‐uniform k ‐space sample density in retrospectively respiratory‐gated lung MRI by uniformly distributing gated radial views across the k ‐space. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : A radial sampling strategy is proposed that can maintain nearly uniform k ‐space coverage after retrospective respiratory gating in 3D lung MRI. The proposed sampling strategy aims to make potential k ‐space holes created by retrospective gating be distributed incoherently so that the point spread function has small and diffused magnitude in side‐lobes, thereby yielding minimal aliasing artifacts. An analytic form of sampling functions with multiple interleaves was proposed for intra‐interleave coherence and the optimal condition was then found for inter‐interleave coherence.